Biphasic spatiotemporal regulation of GRB2 dynamics by p52SHC for transient RAS activation - Yoshizawa, Ryo (Biophys Physicobiol, 2021)
RTK-RAS-MAPK systems are major signaling pathways for cell fate decisions. Among the several RTK species, it is known that the transient activation of ERK (MAPK) stimulates cell proliferation, whereas its sustained activation induces cell differentiation. In both instances however, RAS activation is transient, suggesting that the strict temporal regulation of its activity is critical in normal cells. RAS on the cytoplasmic side of the plasma membrane is activated by SOS through the recruitment of GRB2/SOS complex to the RTKs that are phosphorylated after stimulation with growth factors. The adaptor protein GRB2 recognizes phospho-RTKs both directly and indirectly via another adaptor protein, SHC. We here studied the regulation of GRB2 recruitment under the SHC pathway using single-molecule imaging and fluorescence correlation spectroscopy in living cells. We stimulated MCF7 cells with a differentiation factor, heregulin, and observed the translocation, complex formation, and phosphorylation of cell signaling molecules including GRB2 and SHC. Our results suggest a biphasic regulation of the GRB2/SOS-RAS pathway by SHC: At the early stage (<10 min) of stimulation, SHC increased the amplitude of RAS activity by increasing the association sites for the GRB2/SOS complex on the plasma membrane. At the later stage however, SHC suppressed RAS activation and sequestered GRB2 molecules from the membrane through the complex formation in the cytoplasm. The latter mechanism functions additively to other mechanisms of negative feedback regulation of RAS from MEK and/or ERK to complete the transient activation dynamics of RAS.